2008
DOI: 10.1111/j.1365-2702.2008.02445.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug use and pressure ulcers in long‐term care units: do nurse time pressure and unfair management increase the prevalence?

Abstract: Organisational initiatives should be aimed at reducing time pressures and promoting fair managerial procedures that engage all nursing staff in the decision-making in long-term care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 48 publications
1
34
0
2
Order By: Relevance
“…2006). Time pressure has also been found to increase the prevalence of quality problems in long‐term care (Pekkarinen et al. 2008) and to reduce nurses’ ability to detect the need and the tendency to report intervening (Thompson et al.…”
Section: Introductionmentioning
confidence: 99%
“…2006). Time pressure has also been found to increase the prevalence of quality problems in long‐term care (Pekkarinen et al. 2008) and to reduce nurses’ ability to detect the need and the tendency to report intervening (Thompson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Time pressure was negatively related to patient safety, consistent with the literature's consensus that time pressure reduces the nurses' ability to distinguish relevant signals from irrelevant signals or noise . Other studies similarly found that time pressure also impacted patient perceptions of health-care quality (Pekkarinen et al 2008, Teng et al 2010a.…”
Section: Main Findings and Contributionsmentioning
confidence: 85%
“…Other studies similarly found that time pressure also impacted patient perceptions of health‐care quality (Pekkarinen et al . , Teng et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure ulcers decrease residents' quality of life, while increasing risks of morbidity and mortality (Tannen et al 2009). Higher staffing levels and higher professional staff mix (Bostick 2004, Schnelle et al 2004, supportive work environment (Flynn et al 2010), better teamwork (Eaton 2000) and less time pressure (Pekkarinen et al 2008) have been linked to lower pressure ulcer prevalence. Urinary tract infections (UTI) are the most common infections in NHs, although often asymptomatic.…”
Section: Introductionmentioning
confidence: 99%